2010
DOI: 10.1002/mde.1482
|View full text |Cite
|
Sign up to set email alerts
|

How are prices adjusted in response to shocks? Survey evidence from Austrian firms

Abstract: In this paper we investigate the response of prices to shocks based on a survey of Austrian firms. We find that firms are more likely to change prices after a cost shock than after a demand shock. In this vein, our analysis suggests that regular customers are an important explanation for price rigidity after demand shocks. Furthermore, lacking competition is another significant explanation for price stickiness. Finally, we find asymmetric responses after cost and demand shocks. Prices appear to be more rigid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Case studies, when carried out carefully in relation to well‐identified theoretical questions, are an appropriate way to investigate organizational questions, and may be the only means available to do so in some cases. Our recent special edition on pricing practices (Levy and Smets, 2010) includes several papers (for example, Kwapil et al ., 2010) based on case‐study methods, often augmented with statistical analysis.…”
Section: Trends In Managerial and Decision Economicsmentioning
confidence: 99%
“…Case studies, when carried out carefully in relation to well‐identified theoretical questions, are an appropriate way to investigate organizational questions, and may be the only means available to do so in some cases. Our recent special edition on pricing practices (Levy and Smets, 2010) includes several papers (for example, Kwapil et al ., 2010) based on case‐study methods, often augmented with statistical analysis.…”
Section: Trends In Managerial and Decision Economicsmentioning
confidence: 99%
“…By contrast, our model does not rely on the assumption of trend inflation.3 In their survey,Blinder et al (1998) additionally find clear evidence that the pricing of those firms for which the fear of antagonizing their customers through price changes plays an important role is relatively upward sluggish. Unfortunately, the authors do no distinguish between temporary and permanent shifts in demand in their survey questions.4 Further evidence for OECD countries is provided by, for example,Fabiani et al (2004) for Italy,Loupias and Ricart (2004) for France,Zbaracki et al (2004) for the United States,Alvarez and Hernando (2005) for Spain,Amirault et al (2005) for Canada,Aucremanne and Druant (2005) for Belgium,Stahl (2005) for Germany,Lünnemann and Mathä (2006) for Luxembourg,Langbraaten et al (2008) for Norway,Hoeberichts and Stokman (2010) for the Netherlands,Kwapil et al (2010) for Austria,Martins (2010) for Portugal,Ólafsson et al (2011) for Iceland, andGreenslade and Parker (2012) for the United Kingdom.…”
mentioning
confidence: 98%
“…By contrast, our model does not rely on the assumption of trend inflation.3 In their survey,Blinder et al (1998) additionally find clear evidence that the pricing of those firms for which the fear of antagonizing their customers through price changes plays an important role is relatively upward sluggish. Unfortunately, the authors do no distinguish between temporary and permanent shifts in demand in their survey questions.4 Further evidence for OECD countries is provided by, for example,Fabiani et al (2004) for Italy,Loupias and Ricart (2004) for France,Zbaracki et al (2004) for the United States,Alvarez and Hernando (2005) for Spain,Amirault et al (2005) for Canada,Aucremanne and Druant (2005) for Belgium,Stahl (2005) for Germany,Lünnemann and Mathä (2006) for Luxembourg,Langbraaten et al (2008) for Norway,Hoeberichts and Stokman (2010) for the Netherlands,Kwapil et al (2010) for Austria,Martins (2010) for Portugal,Ólafsson et al (2011) for Iceland, andGreenslade and Parker (2012) for the United Kingdom.…”
mentioning
confidence: 99%